Konstruksi Nilai Pendidikan Sosial dalam Surah Al-Ma’un - Ramadani, Bagas Prasetyo; Purwidianto, Purwidianto; Amrillah, Rizki (LPPPI Publishing, 2024)
Construction of Social Education Values ??in Surah Al-Ma'un. Education and social can’t be separated in a role. Social education plays important role in the formation of social institutions and social environment and its influence on quality of individuals who build society. Through this research, researchers want to reveal the components that make up the value of social education in Surah Al-Maun. The researcher used qualitative methods with descriptive analysis approach from literature review. The compiler also used the Maudu'i method which is a method of interpreting Al-Quran verses based on certain themes or topics discussed in the surah or part of the verse being studied. With this research, it was found that the value of social education in Surah Al-Maun is to build awareness among others, in this case it is emphasized for orphans and the poor by giving alms from the best goods. In this discussion, the interpretation of worship and muamalah must be in harmony. It is concluded that good and correct worship produces individuals who care about society and are not limited to God. So that the results of spiritual relationship have relevance to human aspect, giving rise to tolerance and concern which are the values ??of social education in Surah Al-Maun.